Redesign of a polyclinic as a hospital institution for COVID-19 patients' care. Cienfuegos experiences - Arelys Falcón Hernández; Julio Jova Dueñas; Yanet Pérez Cruz; Pável Rodríguez Moteagudo (Medisur)
This work collects the experiences in the redesign of a municipal Polyclinic as a hospital institution for the care of patients with COVID-19 in the Cienfuegos province. The interventions are detailed in the structural and functional order that allowed the proper functioning of the institution in the face of the new missions assigned within the framework of the COVID-19 epidemic in the province, guaranteeing the workers and patients' safety.